PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PELAJARAN SEJARAH MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS XI IPS 1 SMA NEGERI 11 BANJARMASIN - Riatni Mustaqimah (Universitas Lambung Mangkurat, 2015)
The method used in this classroom action research is qualitative analysis methods, which essentially emphasizes the depiction of business matters related to increasing the activity and learning outcomes of didik.secara depth. The research process started in March until May 2015, the number of samples of 32 people from class XI IPS 1 SMAN 11 Banjarmasin. The results showed that: (1) Activities Teacher for teaching and learning activities using problem-based learning model is considered good and aktif.2. The individual activities rated active power. Seen from the score of the acquisition activity of students in the learning process activity both the first cycle and the second cycle by 3.28 with active classification. 3. Activities group rated active power. The first cycle of activity lasted quite active, with the acquisition of the average score for the group Peta (2.8), Seinendan (3.4), Keibodan (3.2), Heiho (3.0) and Hokokai (3.2). The second cycle there is an increase in the activity of a group of 3 groups of fairly active, namely Map (3.4), Keibodan (3.6) and Heiho (3.6) and two active groups that Seinendan (4.0), Hokokai (4,0) , 4. An increase in student learning outcomes in which the thoroughness of 53.13 increased 40.62 points to 93.75. The increase also in terms of the number of students who complete the first cycle of 17 to 30 people in the second cycle, meaning there was an additional 13 people.Keywords: learning, learning activities, results learning, problem based learning model, history